Keefektifan Media Wayang Profesi Terhadap Keterampilan Bercerita dan Aktualisasi Diri Anak Usia Dini - Anik, Anik Rusmiati; Sagala, Anita Chandra Dewi; Sulianto, Joko (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
Children's storytelling and self-actualization skills are still low, including some children who have not yet mastered the content of the story, are less expressive when telling stories, have less clear voices when telling stories, lack vocabulary, children are less able to approach themselves with their peers, and cannot communicate actively with their peers. friends, and children who have not independently carried out tasks are the background for this research. This research aims to determine the effectiveness of professional wayang media on children's storytelling skills and self-actualization. The method used in this research is the quasi experimental method. Hypothesis testing uses the N-Gain Score test. The results of the N-Gain Score test show that professional puppet media is effective in improving children's storytelling skills and self-actualization.